Analysis of Intelligence Mapping of Brain Tendencies of 8th Grade Students of SMPN 1 Balongan Using Neuroscience - Tita Rizqiyah; Didik Himmawan (Journal Of Psychology, Counseling And Education, 2025)
Research shows that the human brain consists of various parts. Each part has different functions and aspects. In general, we already know that the brain consists of the right brain and the left brain. Where each brain has a different function. This brain tendency mapping analysis was created with the aim of providing an overview for grade 8 students of SMP 1 Balongan to get to know themselves better about what Allah SWT has given to each individual. The method used when conducting the analysis is qualitative research by distributing questionnaires. From the results of this research, it can be seen that many of the 8th grade students at SMP 1 Balongan do not know their own brain tendencies.